The relative importance of work-related and non-work-related stressors and perceived social support on global perceived stress in a cross-sectional population-based sample - Jes Bak Sørensen; Mathias Lasgaard; Morten Vejs Willert; Finn Breinholt Larsen (BMC, 2021)
Abstract Background High levels of perceived stress have a negative bearing on health and well-being, and stress is a major public health issue. According to the Stress Process Model, stressors are socially patterned and combine to produce strain. Despite this, most studies on stress have focused on work-related stressors leaving non-work determinants under-investigated. The aim of the present study was to determine the relative importance of work-related and non-work-related stressors and perceived social support for the overall perceived stress level. Methods Self-reported data were drawn from the 2017 population-based health survey "How are you?" conducted in the Central Denmark Region (N = 32,417). Data were linked with data drawn from national administrative registers. Work- and non-work-related stressors assessed included major life events, chronic stressors and daily hassles. Perceived social support was assessed using a single question. Overall perceived stress was assessed by the 10-item Perceived Stress Scale. We conducted dominance analyses based on a multiple linear regression model to determine the most important explanatory variables of overall perceived stress. Analyses were weighted and adjusted. Results Work- and non-work-related stressors along with perceived social support explained 42.5% of the total variance (R2) in overall perceived stress. The most important explanatory variables were disease, perceived social support and work situation. The stratified analyses produced slightly varying results ("dominance profiles") of perceived stress between subgroups. Work situation was the most important explanatory variable in the employed group. However, adding non-work-related explanatory variables to the analysis tripled the explained variance. Conclusions The overall level of perceived stress can be statistically explained by a combination of work- and non-work-related stressors and perceived social support both at population level and in subgroups. The most important explanatory variables of overall perceived stress are disease, perceived social support and work situation. Results indicate that public health strategies aiming to reduce stress should take a comprehensive approach and address a variety of stressor domains rather than focus on a single domain. Trial registration The study was approved by the Danish Data Protection Agency (r. no. 2012-58-0006) and registered in the Central Denmark Region (r. no. 1-16-02-593-16).